Principles of international economic law / Matthias Herdegen - Herdegen, Matthias
Principles of International Economic Law' provides a comprehensive overview of the central topics in international economic law, with an emphasis on the interplay between the different economic and political interests on both the international and domestic levels. Following recent tendencies, the book sets the classic topics of international economic law, like WTO law, investment protection, commercial law and monetary law in context with aspects of human rights, environmental protection and the legitimate claims of developing countries. The book draws a concise picture of the architecture of international economic law with all its complexities, without getting lost in fragmented details. Providing a perfect introductory text to the field of international economic law, the book thoroughly analyses legal developments within their wider political, economic, or social context. Topics covered range from codes of conduct for multinational enterprises, to the human rights implications of the exploitation of natural resources. The book demonstrates the economic foundations and economic implications of legal frameworks.